2003
DOI: 10.1074/jbc.m206087200
|View full text |Cite
|
Sign up to set email alerts
|

MEK Kinase 1 Interacts with Focal Adhesion Kinase and Regulates Insulin Receptor Substrate-1 Expression

Abstract: MEK kinase 1 (MEKK1) has been shown to contribute to the regulation of cell migration, whereas focal adhesion kinase (FAK) is a major player involved in both cell migration and integrin signaling. Here we show that MEKK1 and FAK are co-immunoprecipitated from mouse fibroblasts. Moreover, the association between MEKK1 and FAK appears to be physiologically relevant, as it is enhanced by treatment with epidermal growth factor (EGF). Targeting FAK to the membrane also enhanced its association with MEKK1, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Also, in cerebellar granule neurons, active JNK is predominantly localized in cytoplasmic compartments (Coffey et al, 2000). Furthermore, active JNK is localized at focal adhesions, and MEKK1, a kinase upstream of JNK, is associated with α-actinin and FAK (Almeida et al, 2000;Christerson et al, 1999;Yujiri et al, 2003). The observations that active JNK is found in cytoplasmic locations provide additional evidence for cytoplasmic functions of JNK, in addition to its established nuclear functions.…”
Section: Jnk Is Involved In Cytoskeleton Reorganizationmentioning
confidence: 62%
“…Also, in cerebellar granule neurons, active JNK is predominantly localized in cytoplasmic compartments (Coffey et al, 2000). Furthermore, active JNK is localized at focal adhesions, and MEKK1, a kinase upstream of JNK, is associated with α-actinin and FAK (Almeida et al, 2000;Christerson et al, 1999;Yujiri et al, 2003). The observations that active JNK is found in cytoplasmic locations provide additional evidence for cytoplasmic functions of JNK, in addition to its established nuclear functions.…”
Section: Jnk Is Involved In Cytoskeleton Reorganizationmentioning
confidence: 62%
“…On the other hand, scaffold protein MEKK1, an upstream mitogen activated protein kinase K (MAPKK) kinase of JNK cascades, is also associated with cytoskeleton reorganization and activated in response to cell volume changes (Kwan et al, 2001;Cross and Templeton, 2004;Lieber et al, 2004). Recent studies found that FAK physiologically inter acts with MEKK1 identified by immunocoprecipitation and co-localization in response to EGF stimulation (Yujiri et al, 2003). Thus, it is very likely in the corneal epithelium that FAK coordinates signals from inputs of UV-induced volume shrinkage to the JNK signaling pathway.…”
Section: Future Developmentsmentioning
confidence: 99%
“…In addition, regulation of FAK phosphorylation by insulin stimulation in non-muscle cells has been reported [8][9][10]. A regulatory role of FAK in IRS-1 levels [11,12] and hepatic insulin action [13,14] has also been reported. Genetic studies have provided evidence for interaction between integrin and insulin signalling [15,16].…”
Section: Introductionmentioning
confidence: 97%